Pengembangan Masyarakat Berwirausaha Desa Pasauran Kecamatan Cinangka Kabupaten Serang - Bambang Hariyanto (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
Administratively, the area of Pasauran Village consists of 4 (four) Community Associations, and 12 (twelve) Neighborhood Associations. In general, Pasauran Village Typology consists of Rice Fields and Farms. Topographic Pasauran Village in general, including lowland areas, and based on the height of the area Pasauran Village is classified to (lowlands (0-100 m above sea level). The total population of Pasauran Village. Based on the Village Profile in 2018 there were 2,957 people consisting of 1,525 men and 1,432 women. The main source of income of the population is from agriculture. Land conditions in Serang Regency are divided into two parts, namely protected areas and cultivation areas. In implementing Thematic KKM in Pasauran Village, KKM students are expected to be able to make programs and strategic plans related to the development of tourism and entrepreneurship areas in Pasauran Village. In addition, KKM students are also expected to be able to realize the tri darma of higher education especially in the fields of entrepreneurship, education and culture in the area.